Multi-User Detection Algorithm for Asynchronous Non-Orthogonal Multiple Access Based on Gaussian Approximation - Peisen WANG; Yueneng WANG; Boming CHENG; Yue YANG; Neng YE (天地一体化信息网络)
Code domain non-orthogonal multiple access (NOMA) is one of the potential technologies to realize ubiquitous access in the future satellite internet.Considering that satellite-to-ground transmission has the characteristics of large propagation delay and high channel dynamics, strict timing synchronization between ground devices will lead to unbearable time resource overhead.Loosed synchronization relationship are required to achieve multi-user access in satellite internet.However, most of the existing multi-user detection algorithms in code domain NOMA are based on the assumption of synchronous transmission, which cannot accurately model and eff ectively alleviate the complex interference introduced by asynchronous multi-user transmission.Therefore, a novel multi-layer factor graph model by introduced the relative delay among users into the traditional two-part factor graph was constructed, and a low-complexity asynchronous multi-user detection algorithm based on gaussian approximation was proposed.The proposed algorithm iterated between each user's estimates and propagated the estimated information between users to improved the approximation.Simulation results showed that in high SNR region, the performance of the asynchronous code-domain NOMA with the proposed algorithm even outperforms its synchronous counterpart.